A liver transplant patient developed renal injury on tacrolimus and experienced worsening renal function and rhabdomyolysis after switching to sirolimus: a case report - Chang Gao; Zhi-Yu Chen; Liang Ma; Shen-Ju Gou (BMC Nephrology)
Abstract Renal impairment and rhabdomyolysis are rare in transplant patients receiving sirolimus. We report the case of a 54-year-old male who underwent liver transplantation and was initially treated with tacrolimus, mycophenolate mofetil, and glucocorticoids for immunosuppression. After the development of renal dysfunction, tacrolimus was replaced with sirolimus. However, one month after taking sirolimus, the patient’s renal function continued to deteriorate, and rhabdomyolysis developed one and a half months later. Serum analysis indicated high sirolimus concentration, whereas renal histopathology revealed acute tubular injury and interstitial arteriopathy. After reducing the dosage of sirolimus, the patient’s creatine kinase levels returned to normal, and renal function improved. Two years after discharge, the patient’s renal function had recovered. This case highlights the importance of monitoring sirolimus blood concentrations in clinical practice, because elevated drug concentrations can lead to renal dysfunction and rhabdomyolysis as adverse reactions. Further investigations into the pathogenic mechanisms of sirolimus-induced renal dysfunction and rhabdomyolysis may contribute to clinical practice.